The Implementation of the Kurikulum Merdeka in Increasing the Self-reliance of Children with Special Needs at Alam Surya Mentari Kindergarten - Inayatullah, Aisyah Rahmah; Astusi, Wili (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to explore how the Kurikulum Merdeka is implemented in increasing the self-reliance of children with special needs at Alam Surya Mentari Kindergarten. Methodology: This study employs a descriptive qualitative approach. Data were collected using triangulation techniques and sources, including interviews, field notes, and documentation. Observations focused on learning activities, teacher-child interactions, and encouragement given to children with special needs. Results: The findings demonstrate how the implementation of the Kurikulum Merdeka contributes to the development of self-reliance in children with special needs. Data from multiple sources showed evidence of both success and ongoing challenges in the curriculum’s application, particularly in fostering autonomy and engagement in inclusive classroom settings. Applications/Originality/Value: This research provides valuable insights into the real-world application of the Kurikulum Merdeka in inclusive education settings. The results can be used to optimize curriculum implementation, enhance motivation and independence in children with special needs, and improve the overall quality of inclusive early childhood education. This evaluation reflects a meaningful effort toward developing a more inclusive, child-centered curriculum.